(untitled) (AmeriQuests, 2022)
The segment of my work containing song lyrics was inspired by a question: Was the Beat Movement an isolated period of thought, tied to one time and location that generated the Beat Generation writers’ unique ideas and inquisitive minds? Certainly, the ideas of the Beats were not confined to one city, or even one country: we can trace their travels to San Francisco, New York, Palo Alto, the Baja Peninsuala, Guatemala, Tangiers, London, Paris, Rome, and places in between. The Beats, like other anti-establishment cultural movements, were tied to an historical moment, in that case post-war America, but their ideas resonate backwards and forwards, from political and artistic revolutions in Europe to the counter-culture movement of the 1960s and 1970s. Their work gave rise to debates in our Beat Generation class as to whether or not our contemporary society could give birth to such a movement. As a group, our class concluded that no, our world today is too digitized and too image-focused to facilitate a counter-culture movement. There is too much media and too much emphasis on consumerism to allow for a mainstream Beat movement. I saw it otherwise, for I am a firm believer that modern Beat ideas exist all around us. It’s easy to find remnants of the Beats in Indie music, and I created a playlist entitled counter-culture baby, inspired by a lyric in Flipturn’s song “Hippies.” Over the course of a few days, I listened to all 158 songs, a total of 9 hours, 38 minutes of music,and I concluded that they lyrics that resonated in my head afterwards expressed similar sentiments to Beat artists. I ultimately chose to include five sets of lyrics in my beat journal, although the album covers of many others are arranged on the preceding and following pages. Moving from top to bottom of the page, there are excerpts from “Vanilla” by Flipturn, “Malibu 1992” by COIN, “Astrovan” by Mt. Joy, “Holy Moly, Rock n’ Rolly, Guacamole” by Lazy Ghost, and “Chicago” by Flipturn. Though many songs in the playlist demonstrated counter-culture and anti-establishment messages, and I thought it was important to choose five songs that resonated with Beat poems. The singers rage against modern America, they expression the fear of a mundane lifestyle, the use of religious figures in an unconventional, pro-freedom manner, and even the creation of new words. Whether these artists know the works of Ginsberg, Kerouac, Burroughs or not, they employ similar techniques and express common ideas throughout their art. As for the segment of cut-ups, one of the goals of the creation of “Être Beat” was to live my life as though I myself was a Beat. I looked at the stars, I debated philosophy late at night, I wrote a manifesto. I sought perspective-altering experiences by going skydiving, learning the bass guitar, and by attending jazz clubs. And in response, I created these works by consciously employing Beat techniques. For instance, I drew inspiration from Gysin and Burroughs in creating a “cut-up” of Verlaine’s poems. I chose Verlaine because his work was often read and discussed in the Beat Hotel. Thus, in as random of a manner as possible, I cut up some of his poems, including but not limited to Chanson à manger, L’angoisse, and Dans les limbes. The result was astounding for me. With scissors and glue, I was able to create ideas I wouldn’t have been able to create with only a pen and paper. Of course, the words are Verlaine’s – but the manner in which they are arranged give them a completely new, abstract, and symbolic meaning.